2015
DOI: 10.1111/vec.12280
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in the use of fresh frozen plasma in critically ill small animal patients

Abstract: The use of FFP in critically ill patients remains controversial. In the absence of clinical bleeding or a risk for clinical bleeding associated with a planned procedure, treatment use of FFP is not recommended in human patients. There are insufficient data in critically ill animals to enable formulation of recommendations. Further research is warranted in dogs and cats to establish evidence-based guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 50 publications
1
25
0
1
Order By: Relevance
“…1 It is used extensively in human medicine with multiple published guidelines. [2][3][4] These guidelines typically recommend administration of FFP for patients with acquired coagulopathies in the presence of active hemorrhage. Examples of such acquired coagulopathies in people include massive transfusion, disseminated intravascular coagulopathy (DIC), liver failure, vitamin K antagonism, and thrombotic thrombocytopenic purpura.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 It is used extensively in human medicine with multiple published guidelines. [2][3][4] These guidelines typically recommend administration of FFP for patients with acquired coagulopathies in the presence of active hemorrhage. Examples of such acquired coagulopathies in people include massive transfusion, disseminated intravascular coagulopathy (DIC), liver failure, vitamin K antagonism, and thrombotic thrombocytopenic purpura.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Coagulopathy is the most common indication, which is consistent with human guidelines. 4 FFP is not indicated for hypoalbuminemia and hypovolemia in multiple human guidelines, 2 which has led to a decrease in veterinary use for these indications. 11 FFP use in cats has been previously reported in subsets of the data of 2 retrospective studies for a total of 38 cats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large retrospective study of dogs and cats undergoing ultrasound‐guided biopsies found that prolongation of activated partial thromboplastin time (aPTT) was a risk factor for bleeding complications in cats, and prolongation of prothrombin time (PT) was a risk factor in dogs, though the numbers of animals experiencing complications even among those with prolonged times was relatively small . Literature suggests that abnormal coagulation test results do not correlate well with clinical bleeding in people, and that evidence supporting a predictable relationship in veterinary medicine is lacking . Thus, further research is needed to generate best practices in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The PT was notably prolonged – 9∙2 and 10∙9 seconds (reference interval 6∙0 to 7∙5 seconds) – in two samples in the DPT group although statistical differences were not detected among the various thawing methods for the measurement of PT. In one of these samples, PTT and factor VII were within normal limits, making a sample collection or handling artefact the most likely cause of the abnormal PT (Smith , Beer & Silverstein , Susan & Rousseau ). In the second sample, both PT and PTT were <25% above outside the reference interval and not considered clinically important.…”
Section: Discussionmentioning
confidence: 99%